Kolaborasi Hijau dalam Tata Kelola Lingkungan Daerah: Refleksi Peringatan Hari Menanam - Ananda, Rizki; Dewi, Citra Septia; Utami, Wahyu Kartiko (Yayasan Daarul Huda Kruengmane, 2025)
Environmental degradation, particularly the decline of forest cover and green open spaces, remains a significant challenge in achieving sustainable regional development. As an effort to enhance public awareness and community participation in environmental conservation, this community service activity was conducted through the commemoration of Indonesia’s Tree Planting Day (Hari Menanam Pohon Indonesia/HMPI) and the National Tree Planting Month (Bulan Menanam Nasional/BMN) in 2025 in Banten Province. This activity aimed to strengthen multi-actor collaboration in regional greening efforts and to encourage active community involvement. The community service was implemented using a collaborative approach involving local government, the NGO Pattiro, the Indonesian National Armed Forces (TNI), the industrial sector, students, and the community. The activities included environmental education, discussions/webinars, and direct tree-planting actions. The results indicate increased cross-sectoral participation, the growth of collective awareness regarding the importance of environmental greening, and the formation of cooperative networks in regional environmental management. However, the sustainability of the activities still faces challenges, particularly related to program continuity and the absence of formal institutional mechanisms to support long-term collaboration. This community service activity demonstrates that multi-stakeholder collaboration is an effective strategy for supporting sustainable environmental governance at the regional level.